Путь к новым успехам в развитии сельского хозяйства - Вершинин Г. (Материалы для лекторов, 1960)
Экземпляры: КР (20020330) / Инвентарный номер: у8384 / Сис.шифр: 63 / Авт.знак: В 37 / ГРНТИ: 68 / ББК: 4